Adiposity and Sex Hormones in Postmenopausal Breast Cancer Survivors - McTiernan, Anne (2003)
PURPOSE: Overweight and obese women with breast cancer have poorer survival compared with thinner women. One possible mechanism is that breast cancer survivors with higher degrees of adiposity have higher concentrations of tumor-promoting hormones. This study examined the association between adiposity and concentrations of estrogens, androgens, and sex hormone binding globulin (SHBG) in a population-based sample of postmenopausal women with breast cancer. METHODS: We studied the associations between body mass index (BMI), body fat mass and percent body fat measured by DXA scan, waist circumference, and waist-to-hip circumference ratio with concentrations of estrone, estradiol, testosterone, SHBG, dehydroepiandrosterone sulfate (DHEAS), free estradiol, and free testosterone in 505 Western Washington and New Mexico postmenopausal women with incident Stage 0-IIIa breast cancer. Blood and adiposity measurements were done between 4–12 months post-diagnosis. RESULTS: Obese women (BMI ≥ 30) had 35% higher concentrations of estrone and 130% higher concentrations of estradiol, compared with lighter women (BMI < 22.0) (p trend, 0.005 and 0.002, respectively). Similar associations were observed for body fat mass, percent body fat and waist circumference. Testosterone concentrations also increased with increasing levels of adiposity (p trend, 0.0001). Concentrations of free estradiol and free testosterone were doubled to tripled in overweight and obese women compared with lighter-weight women (p trend=0.0001). CONCLUSIONS: These data provide information about potential hormonal explanations for the association between adiposity and breast cancer prognosis. These sex hormones may be useful biomarkers for weight loss intervention studies in women with breast cancer.